Start-ups, long- and short-term survivors and their effect on regional employment growth - Michael Fritsch; Florian Noseleit (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
We investigate the effects that regional start-up activity has on employment in new and in incumbent businesses. The analysis is performed for West German regions over the 1987-2002 period. It shows that the effects of new businesses on employment in the incumbents are significantly positive and that this indirect effect on incumbent employment leads to more jobs than what is created by the newcomers. We find that the effect of new business formation on incumbents is exclusively driven by start-ups that survive a certain period of time. We draw conclusions for policy and for further research.
Keywords: L26; M13; O1; O18; R11; 330; Entrepreneurship; new business formation; regional development; direct and indirect effects; Unternehmensgründung; Unternehmensentwicklung; Beschäftigungseffekt; Regionale Entwicklung; Deutschland